Simultaneous Determination of Spirapril and Spiraprilat in Plasma by Capillary Gas Chromatography-Mass Spectrometry - Schürer, Michael; Amschler, Stefan; Schulz, Hans-Ulrich; Schäfer, Harald F. (Arzneimittelforschung, 2003)
A specific, sensitive and precise method for the simultaneous determination of spirapril (CAS 94841-17-5) and spiraprilat (CAS 83602-05-5) in human plasma is described. The method involves the use of enalapril as internal standard, solidphase extraction, derivatization and capillary gas chromatography with mass sensitive detection. The working range is from 2.5 to 500 µg/l for spirapril and spiraprilat, respectively. Data demonstrating the precision and accuracy of the analytical method are given. Moreover, data concerning freeze-thaw stability, longterm stability of frozen samples, shortterm stability of thawed samples, and stability of the extracts in the autosampler are given.
Keywords: CAS 83602-05-5; CAS 94841-17-5; Spirapril, determination in plasma; Spiraprilat, determination in plasma